2022
DOI: 10.1371/journal.pone.0267682
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights gained from cell and molecular analysis of the neuroprotective potential of bioactive natural compounds in an immortalized hippocampal cell line

Abstract: Evaluating novel compounds for neuroprotective effects in animal models of traumatic brain injury (TBI) is a protracted, labor-intensive and costly effort. However, the present lack of effective treatment options for TBI, despite decades of research, shows the critical need for alternative methods for screening new drug candidates with neuroprotective properties. Because natural products have been a leading source of new therapeutic agents for human diseases, we used an in vitro model of stretch injury to rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In vitro cell studies of PTE’s neuroprotective mechanisms found that PTE treatment significantly inhibited the expression of Bdnf and Bcl-2 miRNA and upregulated the expression of miR-702-5p in H19-7 cells. This suggests that PTE protects the nervous system by enhancing cell viability and inhibiting cell apoptosis ( Weisz et al, 2022 ). PTE’s inhibitory mechanism on oxidative stress primarily involves the following: (i) PTE increases the expression level of manganese superoxide dismutase (Mn-SOD) in the mitochondrial matrix by activating Bcl-2 associated X protein, thereby inhibiting mitochondrial respiration and reducing oxide production.…”
Section: Tbi and Pleiotropic Neuroprotective Drugsmentioning
confidence: 99%
“…In vitro cell studies of PTE’s neuroprotective mechanisms found that PTE treatment significantly inhibited the expression of Bdnf and Bcl-2 miRNA and upregulated the expression of miR-702-5p in H19-7 cells. This suggests that PTE protects the nervous system by enhancing cell viability and inhibiting cell apoptosis ( Weisz et al, 2022 ). PTE’s inhibitory mechanism on oxidative stress primarily involves the following: (i) PTE increases the expression level of manganese superoxide dismutase (Mn-SOD) in the mitochondrial matrix by activating Bcl-2 associated X protein, thereby inhibiting mitochondrial respiration and reducing oxide production.…”
Section: Tbi and Pleiotropic Neuroprotective Drugsmentioning
confidence: 99%